2020
DOI: 10.1007/s42399-020-00407-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Options Available for COVID-19 and an Analysis on Possible Role of Combination of rhACE2, Angiotensin (1-7) and Angiotensin (1-9) as Effective Therapeutic Measure

Abstract: Corona virus disease (COVID-19), caused by SARS-CoV-2, is rapidly spreading all around the world and is posing a threat to mankind. Since SARS-CoV-2 is a novel virus, little is known about it and no effective drug is available for its treatment. While many drugs are being evaluated, an effective therapeutic measure is still lacking. SARS-CoV-2 like SARS-CoV binds with angiotensin-converting enzyme 2 (ACE2) present on human cells. SARS-CoV has been found to downregulate ACE2 and SARS-CoV-2 infection has been fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 31 publications
0
25
0
6
Order By: Relevance
“… 22 , 23 Several studies have reported the beneficial and preventive role of therapeutic sACE2 in COVID‐19 21 ,. 24–28 Surprisingly, clinical data suggest that patients with low mACE2 and high sACE2 faced more disease severity and fatality 25 ,. 28 This contrasts with the protective role of therapeutic sACE2 claimed in literature.…”
Section: Introductionmentioning
confidence: 99%
“… 22 , 23 Several studies have reported the beneficial and preventive role of therapeutic sACE2 in COVID‐19 21 ,. 24–28 Surprisingly, clinical data suggest that patients with low mACE2 and high sACE2 faced more disease severity and fatality 25 ,. 28 This contrasts with the protective role of therapeutic sACE2 claimed in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Come già descritto, l'ACE-2 è il recettore di ingresso cellulare della SARS-CoV-2, ed è anche un componente chiave del RAS. Pertanto, una piena comprensione della correlazione tra ACE-2 e SARS-CoV-2 sarebbe di fondamentale importanza per agire con strategie di intervento farmacologico mirate (Ferrara and Vitiello 2020 ; Vitiello and Ferrara 2021d ; Ferrara and Vitiello 2021b ; Muslim et al 2020 ). Tuttavia, sebbene l'ACE-2 sia stato identificato come recettore della SARS-CoV-2, potrebbero esserci altri co-recettori della SARS-CoV-2 ancora da scoprire (Muslim et al 2020 ).…”
Section: Pharmacological Target Of Sars-cov-2unclassified
“…Pertanto, una piena comprensione della correlazione tra ACE-2 e SARS-CoV-2 sarebbe di fondamentale importanza per agire con strategie di intervento farmacologico mirate (Ferrara and Vitiello 2020 ; Vitiello and Ferrara 2021d ; Ferrara and Vitiello 2021b ; Muslim et al 2020 ). Tuttavia, sebbene l'ACE-2 sia stato identificato come recettore della SARS-CoV-2, potrebbero esserci altri co-recettori della SARS-CoV-2 ancora da scoprire (Muslim et al 2020 ). Ciò solleva ulteriori importanti implicazioni per i bersagli terapeutici della SARS-CoV-2 (Marovich et al 2020 ; Vitiello et al 2021d ; Singh et al 2021 ).…”
Section: Pharmacological Target Of Sars-cov-2unclassified
See 1 more Smart Citation
“…Importantly, these excessive levels of Ang-II are linearly associated with SARS-Cov-2 viral load and severity of lung injury during COVID-19 13 , 14 . In addition, the plasma levels of Ang-(1–7) and potentially those of Ang-1–9 [15] are significantly lower in COVID-19 patients than in healthy controls, and these levels are particularly low in COVID-19 patients who are admitted to ICUs. As a consequence, a general imbalance between the ‘harmful’ and ‘protective’ arms of the RAS, resulting from excessive activation of AT1R and limited activation of AT2R and MasR, has been proposed, and this hypothesis is supported by the clinical picture reported in COVID-19 patients [12] .…”
Section: Sars-cov-2 and The Renin–angiotensin Systemmentioning
confidence: 95%